The Northern Sea Route - Taube, Andreas; Bornstein, Martin; Börjesson, Christian (My University, 2012)
This report reviews research on the potential affect cold climate might have on cargoes carried onboard commercial vessels. Due to the recent years’ shrinkage and melting of the sea ice in the Arctic the possibility of a shorter route between Asia and Europe has been enhanced. Companies within the shipping industry hope to benefit from the reduced fuel costs and shorter transit time that the Northern Sea Route (NSR) could offer. With the increased interest from shipping companies, the need for increased knowledge of the potential risks for cargoes has emerged. This report provides an overview of the NSR as well as presenting possible affects on cargoes and related equipment in cold Arctic climate. The research focuses on three primary cargo segments identified as General and Unitised Cargo, Liquid Bulk and Dry Bulk. Information has been gathered by interviewing proficient personnel within the shipping industry such as ship-owners within the different cargo segments, insurance companies with experience and knowledge of potential damage to cargoes, and cargo owners with great knowledge about their cargoes’ properties. We have managed to compile the information into a report that provides a general picture of potential affects within our chosen cargo segments. The risk factors that have been identified in this report have also made us aware of the available solutions. If shipping wants to use the Northern Sea Route as a new commercial shipping route they must be aware of risk factors such as solidification, condensation, and required heating precautions as well as the advantages and disadvantages of the solutions for these problems. It is especially important in such a remote area as the Arctic Ocean, where infrastructure and support are undeveloped. Nevertheless, the common opinion from our interview objects is that there are generally no increased problems to ship cargoes in a cold climate as long as the cargo related gear operates properly. This report will present some cargoes that are examples of specific properties that without certain precautions get affected if transported in a cold climate.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering